2009
DOI: 10.1177/016264340902400304
|View full text |Cite
|
Sign up to set email alerts
|

Expanding Literacy for Learners with Intellectual Disabilities: The Role of Supported eText

Abstract: A series of single-subject experiments were conducted to evaluate the effects of presentational, translational, illustrative, instructional, and summarizing supports on the reading and listening comprehension of students with moderate intellectual disabilities. The specific eText supports under investigation included digitized voice and text-to-speech, text highlighting, video summaries, text-linked photographs, and graphic organizers. Two eText supports were found to be effective in supporting text comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 15 publications
2
23
0
5
Order By: Relevance
“…Douglas, Ayres, Langone, Bell and Meade (2009) examined the use of eText supports to reading and listening comprehension for students with intellectual disability, determining that recorded voice or text-to-speech supports and graphic organizers improved text comprehension. Mechling, Gast, and Thompson (2008) found that the use of SMART board technology in combination with flash card instruction improved acquisition of sight words, both targeted and through observational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Douglas, Ayres, Langone, Bell and Meade (2009) examined the use of eText supports to reading and listening comprehension for students with intellectual disability, determining that recorded voice or text-to-speech supports and graphic organizers improved text comprehension. Mechling, Gast, and Thompson (2008) found that the use of SMART board technology in combination with flash card instruction improved acquisition of sight words, both targeted and through observational learning.…”
Section: Discussionmentioning
confidence: 99%
“…Much more promising is examining areas of reading instruction that utilize traditional best practices, but either pair them with online reading work after teacher instruction [28][29][30] or present traditional reading strategies online [31][32][33][34][35]. Though the results of these studies are far from conclusive, they point to several directions moving forward to support SWSNs in their work in online reading environments around what is already known about quality reading strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Gains were also seen in using computerized graphic organizers for writing. In another study, researchers completed six single-subject investigations with students with high incidence disabilities that utilized targeted online reading environments [29]. Students utilized graphic organizers and screen readers to repeatedly read a story, watch videos, highlight text, and view multiple presentations of instruction.…”
Section: Traditional Instructional Methods With Technologymentioning
confidence: 99%
“…Two of these eText supports were found to have considerable potential for expanding the literacy of participating students: text that was read out loud (using either recorded voice or text-to-speech), and graphic organizers. Their article highlights the challenges of conducting research with this population of students and discusses the potential benefits of increased literacy for students with intellectual disabilities as well as for their teachers and parents (Douglas, Ayres, Langone, Bell, & Meade, 2009). …”
Section: Literacy For Learners With Intellectual Disabilitiesmentioning
confidence: 99%
“…One of the studies investigated the use of supported eText in an online curriculum focused on information literacy skills for high school students (Izzo et al, 2009). And, one of the studies explored ways to expand student literacy by supporting the reading of simplified text from a popular novel and a variety of materials focused on improving independent living and life skills (Douglas et al, 2009). …”
Section: Curriculum Materials and Content Areamentioning
confidence: 99%